Self-similarity problem of thermal convection averaged over a thin layer - Ludmila V. Sakharova (Advanced Engineering Research)
Three types of self-simulated replacements for the problem of thermal convection averaged over a thin layer of the vaporizing liquid are presented. It is a model of the drying non-viscous extended droplet specified by the non-thermal diffusivity. For the construction of self-simulated solutions, a transition to the Riemann invariants is performed. Self-simulated solutions are functions of time and position determining the drop height, the mass-transfer rate and the heat flow averaged over the drop thickness. The found self-simulated solutions are classified on the basis of the behavior of the function that describes the drop height under the evaporation-condensation. The domains of applicability of various self-simulated solutions to the simulation of different situations of drying drops and films are identified.